Establishment of a protein bank, grass cutting and vermiculture in a familiar system of sheep production (Revista Sistemas de Producción Agroecológicos, 2015)
This farming project was developed with the MIMA Foundation, in coordination with UNILLANOS, on Niquia farm located in the village of Indostán, 39 km way Puerto López, in the municipality of Villavicencio-Meta. The soil analysis determines that farm soil is low quality, therefore, needs to be improved through sustainable agricultural practices, fertilization with organic fertilizers and improving its physical structure with earthworms. The study aimed to establish food plots of Tithonia diversifolia and Moringa oleifera, grass cutting (Pennisetum purpureum var. Panamá) and vermiculture in a system of sheep production. 705 stakes were used of Tithonia diversifolia with 30 cm long and 2.5 to 3.5 cm thick, which were planted in polyethylene bags with a capacity of 1 kg, which is filled 3/4 of earth and 1/4 of solid humus, and then transplant it to the definitive site; for protein bank a total area of 240 m2 was used. Moringa seeds were sown in nursery similar manner to the Tithonia diversifolia. In total 1121 plants were sown in an area of 1440 m2, distributed in two lots and 15.5 packages (40 kg c/u) of solid humus were used when they transplanted to the definitive site. The production of fresh material on the first and second batch was 250 and 190 g/plant respectively. The planting area of Pennisetum purpureum var. Panamá was 1060 m2, and all harvested was about 4.5 tons, with a production of 4 kg/m2. The vermiculture has proven to be a key strategy in developing the project, because the humus is used to fertilize crops, furthermore the external sale generates additional cash income, therefore, this technology contributes to solve two of the environmental problems they face today: the accumulation of high concentrations of organic waste on farms and the need of organic matter in agricultural soils.
Keywords: Sheep; Moringa oleifera; Tithonia diversifolia; Eisenia foetida; organic fertilizer